Going It Alone : Ramblings and Reflections from the Trail - Hauserman, Tim, 1958- (Book collections on Project MUSE., 2022)
"Solo is the story of the conflict between joy and loneliness Tim Hauserman discovered on a series of backpack trips in the wilderness: a tale of self-induced misadventures and overwhelming sadness but also many moments of sublime rapture. It is a humorous, humble take on the experience of spending time alone in the wilderness-part exquisite nature journal, part Bill Bryson in the woods- with a unique voice and take on the world"--